LiDAR and other evidence for the southwest continuation and Late Quaternary reactivation of the Norumbega Fault System and a cross-cutting structure near Biddeford, Maine, USA - Marple, Ronald T.; Hurd Jr., James D. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2019)
High-resolution LiDAR (light detection and ranging) images reveal numerous NE-SW-trending geomorphic lineaments that may represent the southwest continuation of the Norumbega fault system (NFS) along a broad, 30- to 50-km-wide zone of brittle faults that continues at least 100 km across southern Maine and southeastern New Hampshire. These lineaments are characterized by linear depressions and valleys, linear drainage patterns, abrupt bends in rivers, and linear scarps. The Nonesuch River, South Portland, and Mackworth faults of the NFS appear to continue up to 100 km southwest of the Saco River along prominent but discontinuous LiDAR lineaments. Southeast-facing scarps that cross drumlins along some of the lineaments in southern Maine suggest that late Quaternary displacements have occurred along these lineaments. Several NW-SE-trending geomorphic features and geophysical lineaments near Biddeford, Maine, may represent a 30-km-long, NW-SE-trending structure that crosses part of the NFS. Brittle NWSE-trending, pre-Triassic faults in the Kittery Formation at Biddeford Pool, Maine, support this hypothesis.